2018
DOI: 10.1111/ijd.14005
|View full text |Cite
|
Sign up to set email alerts
|

Bullous pemphigoid induced by dipeptidyl peptidase‐4 inhibitors. Eight cases with clinical and immunological characterization

Abstract: Patients with DPP-4 inhibitor-induced BP may present either an inflammatory or a noninflammatory phenotype of BP. IgG response against other BP180 regions different from the NC16A domain, such as LAD-1 and the C-terminal domain, could be pathogenically relevant to the onset of DPP-4 inhibitor-induced BP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
1
7

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 32 publications
(47 reference statements)
2
35
1
7
Order By: Relevance
“…The mean latency between the initiation of gliptin treatment and diagnosis of BP was approximately 13 months, which is in line with the findings of the recent registry studies (14,16). As in most previous reports (17,23,36) gliptins were withdrawn from most of our patients when they were diagnosed with BP, and all but one, required systemic treatment. Discontinuation of DPP-4i treatment is supported by studies, which demonstrated that gliptin withdrawal was followed by an improvement of BP clinical outcomes (14).…”
Section: Discussionsupporting
confidence: 90%
“…The mean latency between the initiation of gliptin treatment and diagnosis of BP was approximately 13 months, which is in line with the findings of the recent registry studies (14,16). As in most previous reports (17,23,36) gliptins were withdrawn from most of our patients when they were diagnosed with BP, and all but one, required systemic treatment. Discontinuation of DPP-4i treatment is supported by studies, which demonstrated that gliptin withdrawal was followed by an improvement of BP clinical outcomes (14).…”
Section: Discussionsupporting
confidence: 90%
“…Most BP patients present autoantibodies which bind to the 180-kDa protein immunodominant region, referred to as the non-collagenous domain NC16A [9,10]. However, in patients with gliptin-induced BP, most of these autoantibodies have been reported to react to other sites of the BP180 protein, such as LAD-1 and/or the terminal carboxyl domain [11]. To our knowledge, no specific BP drug-inducing autoantibodies have been identified yet.…”
Section: Introductionmentioning
confidence: 98%
“…Among the side effects of gliptins involving the skin, itching, urticaria, and Stevens‐Johnson syndrome stand out. Many research publications have shown the association between gliptins and PB. It has also been described in the literature one case of bullous LP secondary to nivolumab and another one case probably caused by enalapril .…”
Section: Differential Diagnosis Of Lp Pemphigoid and Main Differencesmentioning
confidence: 99%